Rare appearance of an odontogenic myxoma in cone-beam computed tomography: a case report - Arash Dabbaghi; Nafiseh Nikkerdar; Soheyla Bayati; Amin Golshah (Tabriz University of Medical Sciences, 2016)
Odontogenic myxoma (OM) is an infiltrative benign bone tumor that occurs almost exclusively in the facial skeleton. The radiographic characteristics of odontogenic myxoma may produce several patterns, making diagnosis difficult. Cone-beam computed tomography (CBCT) may prove extremely useful in clarifying the intraosseous extent of the tumor and its effects on surrounding structures. Here, we report a case of odontogenic myxoma of the mandible in a 27-year-old female. The patient exhibited a slight swelling in the left mandible. Surgical resection was performed. No recurrence was noted. In the CBCT sections, we observed perforation of the cortical plate and radiopaque line that extended from the periosteum, resembling "sunray" appearance-a rare feature of OM-which could not be assessed by panoramic radiography.